2013
DOI: 10.1111/ppa.12120
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the F129L mutation in Alternaria solani populations in Germany in response to QoI application, and its effect on sensitivity

Abstract: Early blight caused by Alternaria solani is a highly destructive disease of potatoes. Control of early blight mainly relies on the use of preventive fungicide treatments. Because of their high efficacy, azoxystrobin and other quinone outside inhibitors (QoIs) are commonly used to manage early blight. However, loss of sensitivity to QoIs has previously been reported for A. solani in the United States. Two hundred and three A. solani field isolates collected from 81 locations in Germany between 2005 and 2011 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 26 publications
5
56
1
1
Order By: Relevance
“…The shift to reduced sensitivity also tended to be more pronounced in isolates with the F129L substitution collected in 2014 compared to isolates from 2011, indicating that application of QoI fungicides has resulted in reduced sensitivity of the isolates over time. These results are in accordance with the previous study [19], which also reported that isolates carrying this substitution had reduced in vitro sensitivity to QoI fungicides, especially against azoxystrobin.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The shift to reduced sensitivity also tended to be more pronounced in isolates with the F129L substitution collected in 2014 compared to isolates from 2011, indicating that application of QoI fungicides has resulted in reduced sensitivity of the isolates over time. These results are in accordance with the previous study [19], which also reported that isolates carrying this substitution had reduced in vitro sensitivity to QoI fungicides, especially against azoxystrobin.…”
Section: Discussionsupporting
confidence: 93%
“…In Europe, A. solani isolates containing the F129L substitution were first found in Germany. Isolates possessing the substitution also displayed a shift in sensitivity to different strobilurins in in vitro spore germination assays [19]. None of the Swedish GI isolates carried the F129L substitution, while the F129L substitution was observed in many of the GII isolates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations